Tuberculous peritonitis with elevated serum CA125 levels mimicking peritoneal cancer - A. Taniwaki; Y. Hashiguchi; M. Yamauchi; M. Kasai; T. Fukuda; T. Ichimura; T. Yasui; T. Sumi (IMR Press, 2020)
Background: Tuberculosis can spread to the peritoneum through the gastrointestinal tract via mesenteric lymph nodes or directly from the blood, lymph, or fallopian tubes. Tuberculous peritonitis can mimic pelvic or intra-abdominal malignancies, making the diagnosis of this disease difficult. Case: A 32-year-old female presented with tuberculous peritonitis that mimicked peritoneal cancer. Our patient presented with general fatigue, weight loss, and diarrhea, which had started 3 months prior. On examination, a thickened peritoneum and ascites, without bilateral adnexal masses, and elevated serum CA125 levels were detected. Peritoneal cancer was initially considered as the most likely diagnosis. An exploratory laparoscopy was performed, and a thickened peritoneum and whitish miliary nodules scattered throughout the abdominal cavity, including the surface of the uterus and adnexa were found. The pathological examination of the frozen resected nodule specimen showed an epitheloid granuloma. We diagnosed the patient with tuberculous peritonitis, which was established postoperatively. Conclusion: If peritoneal cancer is suspected in patients without abnormal cytology of the ascites, early exploratory laparoscopy should be performed to rule out tuberculous peritonitis in the differential diagnosis of patients with peritoneal cancer.